2009
DOI: 10.1299/jcst.3.212
|View full text |Cite
|
Sign up to set email alerts
|

Stress Intensity Factor for a Planar Interfacial Crack in Three Dimensional Bimaterials

Abstract: In this paper, stress intensity factors for a three dimensional planar interfacial crack are considered on the idea of the body force method. The formulation leads to a system of singular integral equation, whose unknowns are three types of crack opening displacements. The unknown body force densities are approximated by the products of the fundamental density functions and power series; here, the fundamental density functions are chosen to express singular stress fields due to a two-dimensional interface crac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…In the preceding papers [12], [13], it is found that the stress intensity factors are controlled by bimaterial constant ε alone under tensile loading. In Table 3, Poisson's ratio and shear modulus ratio are changed under constant value of ε =0.02.…”
Section: The Stress Intensity Factors Under the Same Value Of εmentioning
confidence: 96%
See 1 more Smart Citation
“…In the preceding papers [12], [13], it is found that the stress intensity factors are controlled by bimaterial constant ε alone under tensile loading. In Table 3, Poisson's ratio and shear modulus ratio are changed under constant value of ε =0.02.…”
Section: The Stress Intensity Factors Under the Same Value Of εmentioning
confidence: 96%
“…In the preceding papers [12], [13], a rectangular crack under tension was analyzed and smooth distributions of SIFs were obtained. Although the problem of an interface crack in a dissimilar material is expressed as a system of singular integral equations by Chen-Noda-Tang [14], it is difficult to solve the equations precisely considering the overlap of crack opening displacement and stress oscillation singularity, which are peculiar to interfacial cracks.…”
Section: Introductionmentioning
confidence: 99%